2020
DOI: 10.1007/s00415-020-10134-9
|View full text |Cite
|
Sign up to set email alerts
|

What guides decision-making on intravenous thrombolysis in acute vestibular syndrome and suspected ischemic stroke in the posterior circulation?

Abstract: Intravenous thrombolysis (IVT) is rarely performed in dizzy patients with acute vestibular syndrome (AVS) or acute imbalance (AIS) even if posterior circulation stroke (PCS) is suspected. Decision-making may be affected by uncertainties in discriminating central from peripheral vestibulopathy or concerns of IVT-related harm, particularly intracerebral hemorrhage (ICH), but related studies are missing. Using an in-house register of dizzy patients coming to the emergency room, we identified 29 AVS/AIS patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
0
16
0
4
Order By: Relevance
“…Similar to the latter study, nonexperts revealed high sensitivity (88%) for VN but at the cost of low specificity (64%), reflected by many false‐abnormal bHITs in PCS. Although this may constitute only a minor problem in an elective outpatient visit, it represents a major fault in the emergency setting where a stroke must not be missed, as early treatment and monitoring is mandatory [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the latter study, nonexperts revealed high sensitivity (88%) for VN but at the cost of low specificity (64%), reflected by many false‐abnormal bHITs in PCS. Although this may constitute only a minor problem in an elective outpatient visit, it represents a major fault in the emergency setting where a stroke must not be missed, as early treatment and monitoring is mandatory [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…As shown by our additional analysis, a higher cutoff (0.8) can indeed increase the algorithm's sensitivity for peripheral vestibulopathy but at the same time reduces its specificity, thereby increasing the risk to falsely classify a stroke patient's VOR as abnormal/peripheral. Especially when evaluating AVS patients in an emergency setting, identification of stroke is most critical for clinical decision-making on diagnostics, monitoring and therapy (35). For this population and clinical setting, we [and others (25)] suggest to use the 0.7 as a more conservative cutoff gain for pathological VOR.…”
Section: Discussionmentioning
confidence: 99%
“…If the VOR gain of at least one side is equal or below 0.7, patients should be stratified to the suspected diagnosis of peripheral vestibulopathy and not undergo further stroke-related diagnostics, as this can save imaging and monitoring resources or even unnecessary hospitalization. In contrast, those with a bilateral VOR gain above 0.7 should be assigned to "suspected PCS" and accordingly receive the necessary stroke assessment including brain imaging, monitoring on a stroke unit and where appropriate antiplatelet/anticoagulatory medication, and in severe cases should also be evaluated for potential eligibility for intravenous thrombolysis (35).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that the sensitivity of CT for the detection of acute PCS is low (52) and that a negative CT may lead to false reassurance and missed stroke diagnoses in the emergency setting, especially in patients with less severe or inconclusive symptoms (53). To some extent, this disadvantage is attenuated when multimodal CT-imaging (CT angiography and CT perfusion) is employed, as reported for patients with acute vestibular syndrome who received intravenous thrombolysis triggered by information supplied by these procedures (54). One study found that while there were lower rates of early ischemic signs on admission CT and overall arterial pathology in PCS than in ACS, intracranial arterial pathology was more prevalent in the former (49).…”
Section: The Risk Of False-negative Neuroimaging Of the Posterior Fossamentioning
confidence: 99%